Process management and its relationship with the strategic plan in the context of modernization of public administration peruvian - Begazo Villanueva, José Domingo (2017)
This paper addresses the importance and validity of Process Management, a technique that would provide multiple benefits in the management of organizations, specifically in Public Administration. In Peru, its implementation is a major challenge to the power framed within the National Policy Modernization of Public Management in compliance with the requirements of the Law 27658. The document aims to theoretically support the process management as a key element for achieving organizational success in state institution; the method used is mainly based on the literature review and study of theoretical methods to reveal the essential relationships of process management. date concepts, classification, basic assumptions and relationships in this category are exposed. Provides useful information for managers referring the application of process management, its generalities importance for identifying and solving problems, continuous control over individual processes and process system itself as well as its relationship with quality management, so that highlights the impact of this technique on the success of Public management.